Assessing Information Security Readiness in Indonesian Fintech Companies Using KAMI Index 5.0 Framework - Lestari, Merryana; Puspita, Maria Entina; Geasela, Yemima; Wijaya, Agustinus Fritz; Hiskiawan, Puguh; Vicky, Vicky (Fakultas Ilmu Komputer, Universitas Klabat, 2025)
The development of Indonesian financial technology (fintech) has transformed the financial industry paradigm but has also introduced significant information security risks, particularly for technology-based companies. The fintech companies should establish IT governance through an Information Security Management System (ISMS) which adheres to international standards, ensuring the confidentiality, integrity, and availability of information. This work adopts a qualitative approach deploying observations, interviews, and literature reviews on Indonesian fintech companies, especially digital banking fields, payment gateways, and digital wallet platforms. This study is to identify information security risks and assess the readiness and feasibility of implementing ISO/IEC 27001:2022 using the KAMI Index 5.0, which evaluates domains such as policy, governance, risk management, access control, incident management, asset management, and personal data protection. The research findings indicate that the electronic system of fintech companies plays a strategic role in supporting sustainability and business growth, with an implementation score of 809 and a fairly good level of information security feasibility. In conclusion, this reflects the company’s readiness for further information security implementation. The system not only supports basic operations but also serves as a key element in achieving business objectives, both internally and externally, including regulators, banking partners, and customers.